Manajemen Kurikulum dalam Bingkai Moderasi Beragama di Era Digital di Ma’had Al-Jami’ah Ulil Absar IAIN Ponorogo - Yuliani, Bustanul (Proceedings of Annual Conference for Muslim Scholars, 2022)
The political position in the Islamic struggle was shifted by the emergence of the da'wah movement as an alternative political movement to realise the idea of ​​​​Islamic struggle. These new developments encourage the emergence of new developments of political thought among young people. Thus, it is necessary to strengthen the religious perspective that does not lean towards young people's extreme right or left. At IAIN Ponorogo, students who participate in the ma'had program are given the provisions included in the curriculum of Ma'had Al-Jami'ah Ulil Absar. Students who join the ma'had program are known as mahasantri. They are expected to develop themselves and compete in the digitalization era without leaving their Islamic creed. This paper will discuss curriculum management in the religious moderation framework in the digitalization era at Ma'had Al-Jami'ah Ulil Absar IAIN Ponorogo. This article employs descriptive-qualitative research. It provides descriptions of the field's background, characteristics, and distinctive characters. The data describes the description of the activities or behaviour of the subject and other documents obtained through interviews, observation and documentation. The results showed that general curriculum management within the framework of religious moderation includes planning, organizing, implementing and evaluating curriculum. The religious moderation program was actualized online every Saturday, guided by Muallim, who already have a certificate of religious moderation. Even though there are many obstacles in learning religious moderation online, it does not dampen the enthusiasm of the students to continue learning and participating in religious moderation studies with the hope that students will be able to understand and practice religion side by side with other religions without any religious disputes and be able to spread Islam digitally.